From international travelling consumer to place ambassador: Connecting place image to tourism satisfaction and post-visit intentions. Issue 3 (8th May 2017) - De Nisco, Alessandro; Papadopoulos, Nicolas; Elliot, Statia
Abstract : Purpose: The purpose of this paper is to extend international marketing theory by examining country image effects simultaneously from the perspectives of Product-Country Image (PCI), Tourism Destination Image (TDI), and General Country Image (GCI), and by using tourism satisfaction as the central construct in a comprehensive model that investigates post-visit effects in both the product and tourism domains. Design/methodology/approach: International tourists from multiple countries were intercepted at the end of a tourism trip and interviewed in-person using a structured questionnaire, resulting in 498 usable responses for data analysis. The model comprised seven constructs measured with 28 variables and was tested with structural equation modelling. Findings: The study uncovers a number of cross-effects between a country as destination and as producer, and establishes tourism satisfaction as a core construct that is relevant to both the tourism and product facets of place image. Practical implications: Above all, the study's findings argue strongly in favour of greater coordination between the "product" and "tourism" sides of place marketing. Originality/value: The study is original in its integrative analysis of GCI, PCI, and TDI constructs as antecedents and consequences of the tourism experience and, among other original contributions, is the first to investigate the direct link between product beliefs, tourism satisfaction, and post-visit product-related intentions.